Lesch-Nyhan Syndrome: a rare disorder of self-mutilating behavior - Mrinal Gupta; Vikram K. Mahajan; Vikas Sharma; Pushpinder S. Chauhan; Karaninder S. Mehta (Our Dermatology Online, 2014)
This paper describes Lesch-Nyhan syndrome in a 1-year-old boy. This X-linked recessive error of purine metabolism presents in infancy with a constellation of mental and developmental retardation, self-mutilating behavior, neurological features and abnormal urine uric acid: creatinine ratio. The basic defect is deficiency in phosphoribosyl transferase production but exact pathomechanism for clinical symptomatology remains un-elucidated. No specific medical treatment is available.